A rare case of metaplastic carcinoma of breast - S., Sivaranjani; Akhter, Jameel; ., Kathirazhagan (International Surgery Journal, 2022)
Breast carcinoma is one of the most common cancers among women. There are different types of breast carcinoma that affects female such as localised, invasive ductal/lobular, advanced type. All of them can be managed with standard treatment and it has got variable prognosis. Yet there is another type of breast carcinoma with worst prognosis, low survival rate which does not have proper standard management, it is called as metaplastic carcinoma. We had a 60-year-old postmenopausal female who was diagnosed with metaplastic breast carcinoma managed by simple left mastectomy and Lattissmus dorsi flap.